Answer:
Brooooo im stuck on the same one.
Step-by-step explanation:
Answer:
It increases
Step-by-step explanation:
PLZZ mark brainliest!!!
Answer:
−2=−2x^3
Step-by-step explanation:
10x3= 3x2−20x−6=(10x3⋅(3x2))(−20x−6)=−600x6−180x5x2=−600x6−180x5−2x⋅(2x2)=−4x3−2x⋅x2=−2x^3
−2=−2x3
2x^2=−2x^3
−2=−2x^3
I=prt
I interest earned
P principle 4000
R interest rate 0.095
T time270/365
I=4,000×0.095×(270÷365)
I=281.10
Step-by-step explanation:
y = ax^n + bx^(n-1) ... + z
(0, 1) tells us that the constant term z = 1.
because x = 0 eliminates all other terms. and as the sum is 1, that means z = 1.
for the other pairs I strongly suspect
(-1, 3) : 2×(-1)² + 1 = 2×1 + 1 = 3
(-2, 9) : 2×(-2)² + 1 = 2×4 + 1 = 9
so, the fitting equation is
y = 2x² + 1